MASALAH KEMISKINAN DAN STRATEGI PEMBERDAYAAN MASYARAKAT JAKARTA - Gumilar Rusliwa Somantri (JIP ( Jurnal Industri dan Perkotaan ), 2006)
Poverty is one of the problems which often shadowing the growth of city. Integration the city toward global economic system, has stimulated economic growth and prosperity for Urban citizen.